2009
DOI: 10.1124/mol.109.056317
|View full text |Cite
|
Sign up to set email alerts
|

Controls of Tonic and Phasic Dopamine Transmission in the Dorsal and Ventral Striatum

Abstract: Dopamine (DA) release varies within subregions and local environments of the striatum, suggesting that controls intrinsic and extrinsic to the DA fibers and terminals regulate release. While applying fast-scan cyclic voltammetry and using tonic and phasic stimulus trains, we investigated the regulation of DA release in the dorsolateral to ventral striatum. The ratio of phasic-to-tonic-evoked DA signals varied with the average ongoing firing frequency, and the ratio was generally higher in the nucleus accumbens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
179
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(204 citation statements)
references
References 55 publications
23
179
2
Order By: Relevance
“…Although there are other potential mechanisms for these behavioral effects, they do appear analogous to those demonstrating opposing influences of mAChR and nAChR activity on phasic striatal dopamine release. In the slice, blockade of striatal nAChRs located presynaptically on dopamine terminals (Jones et al, 2001) can modulate the release of dopamine in a manner dependent upon the stimulated firing pattern of dopamine neurons (Zhang and Sulzer, 2004;Zhang et al, 2009). Under some conditions, inactivation of these nAChRs can actually augment the release of dopamine generated by high-frequency stimulation (simulating burst firing) (Rice and Cragg, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are other potential mechanisms for these behavioral effects, they do appear analogous to those demonstrating opposing influences of mAChR and nAChR activity on phasic striatal dopamine release. In the slice, blockade of striatal nAChRs located presynaptically on dopamine terminals (Jones et al, 2001) can modulate the release of dopamine in a manner dependent upon the stimulated firing pattern of dopamine neurons (Zhang and Sulzer, 2004;Zhang et al, 2009). Under some conditions, inactivation of these nAChRs can actually augment the release of dopamine generated by high-frequency stimulation (simulating burst firing) (Rice and Cragg, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Activating presynaptic nAChRs on dopamine terminals with endogenous acetylcholine can trigger dopamine release (Cachope et al, 2012;Threlfell et al, 2012), but ex vivo studies have demonstrated that this modulation depends on the activity level of dopamine cells (Zhang and Sulzer, 2004;Zhang et al, 2009). Nicotinic acetylcholine receptors can facilitate low probability dopamine release, but suppress dopamine release from high-frequency stimulation (mimicking burst firing) (Exley and Cragg, 2008b;Sulzer et al, 2016;Threlfell and Cragg, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These stimulation parameters were selected to model the different in vivo firing patterns of DA neurons; one-pulse stimulations are thought to mimic tonic-like signaling while five-pulse, 20 Hz and 24-pulse, 60 Hz stimulations are thought to mimic phasic-like signaling (Zhang et al, 2009;Daberkow et al, 2013). One-pulse stimulations were applied to the tissue every 5 min until a stable baseline was established (three collections within 10% variability).…”
Section: Methodsmentioning
confidence: 99%
“…However, evidence for this "global" signaling scheme from neurochemical recordings within the striatum itself is lacking. In fact, recent studies with natural rewards have challenged the concept of uniform phasic dopamine signaling throughout the striatum, instead reporting dopamine release in the VMS in response to natural rewards and associated cues but little or no dopamine release in the DLS (18,19).…”
mentioning
confidence: 99%